Analysis of cyber-attacks on smart grid applications - Gunduz, M. Zekeriya; Das, Resul (2018 International Conference on Artificial Intelligence and Data Processing (IDAP), 2018)
Cyber-security is the whole process of preventing damage to the confidentiality, integrity, and availability of information assets as a result of the use of vulnerabilities in information assets by threats. So, confidentiality, integrity, and availability (CIA) which are the key elements of the cyber-security must be provided properly. One of the biggest problems in implementing today's critical infrastructures is the cyber security threats and cyber-attacks. Smart grids stand out in terms of providing efficiency in the generation, transmission, and distribution of electrical energy which is the main element of critical infrastructures. The widespread use of the smart grids requires to identify and classify the threats also precautions to be taken against them. Affected of smart grids at the minimum level by cyber attacks requires that the essential elements of information security must be provided at the maximum level. In this context, in the study; Attacker types, attack types in smart grids and huge cyber-attacks on power systems are introduced. Furthermore, the key objectives and requirements of cyber-security in smart grids are presented. Also, attack types that can be performed in smart grids are classified according to confidentiality, integrity and availability principles. Lastly, the study is evaluated.